Neuraminidase1 Inhibitor Protects Against Doxorubicin-Induced Cardiotoxicity via Suppressing Drp1-Dependent Mitophagy - Qin, Yating; Lv, Chao; Zhang, Xinxin; Ruan, Weibin; Xu, Xiangyu; Chen, Chen; Ji, Xinyun; Lu, Li; Guo, Xiaomei (Frontiers in Cell and Developmental Biology, 2021)
Anthracyclines, such as doxorubicin (DOX), are among the effective chemotherapeutic drugs for various malignancies. However, their clinical use is limited by irreversible cardiotoxicity. This study sought to determine the role of neuraminidase1 (NEU1) in DOX-induced cardiomyopathy and the potential cardio-protective effects of NEU1 inhibitor oseltamivir (OSE). Male Sprague-Dawley (SD) rats were randomized into three groups: control, DOX, DOX+OSE. NEU1 was highly expressed in DOX-treated rat heart tissues compared with control group, which was suppressed by OSE administration. Rats in DOX+OSE group showed preserved cardiac function and were protected from DOX-induced cardiomyopathy. The beneficial effects of OSE were associated with suppression of Drp1-dependent mitochondria fission and mitophagy. In detail, the elevated NEU1 in cardiomyocytes triggered by DOX increased the expression of Drp1, which subsequently enhanced mitochondria fission and PINK1/Parkin pathway-mediated mitophagy, leading to a maladaptive feedback circle towards myocardial apoptosis and cell death. OSE administration selectively inhibited the increased NEU1 in myocardial cells insulted by DOX, followed by reduction of Drp1 expression, inhibition of PINK1 stabilization on mitochondria and Parkin translocation to mitochondria, thus alleviating excessive mitochondria fission and mitophagy, alleviating subsequent development of cellular apoptotic process. This work identified NEU1 as a crucial inducer of DOX-induced cardiomyopathy by promoting Drp1-dependent mitochondria fission and mitophagy, and NEU1 inhibitor showed new indications of cardio-protection against DOX cardiotoxicity.